Analysis of lattice steel towers using STAAD pro - Ahmed S.; Maiti P.R. (My University, 2025)
Free-standing lattice towers have been used extensively as civil engineering structures. Full scale investigations are required for understanding a lattice tower response to wind loading and other loadings. Free-standing lattice towers used for power transmission line, communications and broadcasting tower are often designed by minimum deflection requirements under serviceability conditions. It is possible to predict the probable load-carrying capacity of a tower and instability in the structure. The design objective of lattice tower is to fulfilling the stability criterion and sustainability in worst environmental conditions. The transmission line towers are designed against failure containment loads comprising of anti cascading loads and tensional and longitudinal loads. In the present paper an overview of analysis procedure of lattice structure is presented. Analysis details of communication towers are discussed as per IS code. A model of communication tower is analysed by STAAD pro software and step by step analysis procedure is discussed. The critical design aspects are highlighted for economic modelling requirement of these structures. © Research India Publications.